2011
DOI: 10.1002/jso.21899
|View full text |Cite
|
Sign up to set email alerts
|

Irreversible electroporation of the pancreas: Definitive local therapy without systemic effects

Abstract: This animal model demonstrates that IRE of the pancreas performed at an optimal voltage is well tolerated, with rapid resolution of pancreatic inflammation and preservation of vascular structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
90
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(98 citation statements)
references
References 26 publications
2
90
2
Order By: Relevance
“…This is underlined by the fact that there was no significant change in serum amylase levels in our patients in the first and second postoperative week compared to the preoperative levels. This observation is consistent with findings by bower et al who showed that the serum levels of pancreatic enzymes show only a transient mild increase early in the first postoperative week [11,12]. even though there was no laboratory evidence of acute pancreatitis after ire, postoperative ct showed signs of various degrees of peripancreatic inflammation in the majority of patients.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is underlined by the fact that there was no significant change in serum amylase levels in our patients in the first and second postoperative week compared to the preoperative levels. This observation is consistent with findings by bower et al who showed that the serum levels of pancreatic enzymes show only a transient mild increase early in the first postoperative week [11,12]. even though there was no laboratory evidence of acute pancreatitis after ire, postoperative ct showed signs of various degrees of peripancreatic inflammation in the majority of patients.…”
Section: Discussionsupporting
confidence: 92%
“…unlike thermal ablation techniques, ire poses a minimal risk of damaging adjacent vascular structures or inducing pancreatitis [11]. This is underlined by the fact that there was no significant change in serum amylase levels in our patients in the first and second postoperative week compared to the preoperative levels.…”
Section: Discussionmentioning
confidence: 53%
“…It has been clearly demonstrated that the effectiveness of LEDC is highly associated with the distribution of the electric field in the tissue (with the contributing variables including voltage, distance between the electrodes and depth of electrodes insertion) required to reach the optimal electrode configuration and tumor coverage [3,10,36,38,39,40,41]. Irreversible electroporation aims to completely extirpate the tumor or, at least, to dramatically modify the neoplastic microenvironment without damaging the surrounding tissues or vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this process leads to the creation of nanopores with a disruption of the lipid bilayer and cell death, due to apoptosis, preserving the underlying extracellular matrix [5,6,7,8,9,10,11]. Consequently, IRE has begun to emerge as an important ablation technique, that unlike radiofrequency [12] and microwave or laser [13] does not require the application of thermal energy, thereby preserving sensitive structures located near the tumor, such as nerves, bile ducts, vessels, and the gastrointestinal tract [14,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Based on initial animal and case report studies [71] [72], a small series of 14 patients with unresectable tumors have been treated by IRE. Two patients ultimately underwent surgery and were disease free at 11 and 14 months.…”
Section: Pancreasmentioning
confidence: 99%